THE ROLE OF SOCIOLOGY TEACHER IN OVERCOMING STUDENTS LEARNING DIFFICULTIES AT SMA NEGERI 2 SAMBI RAMPA - Rahmawati; Imrayani (SocioEdu: Sociological Education, 2023)
The objectives of the study were to determine the role of sociology teachers and the factors that impede overcoming students with learning difficulties at SMA Negeri 2 Sambi Rampas. This study employs a qualitative method. The informants were sociology teachers and students who had learning difficulties. Data for the research was collected through observation, interviews, and documentation. This study employs qualitative analysis techniques that revolve around data collection, data reduction, and drawing conclusions. According to the findings, the role of the sociology teacher in overcoming learners who have learning difficulties was becoming a source of inspiration, providing motivation, facilitating learning, guiding, and managing classrooms that are comfortable for students to learn in. Furthermore, the factors that cause students to experience difficulties in learning are the decreased interest in learning, the influence of online games, the lack of desire or willingness of students to learn and learning facilities that are inadequate and poorly managed.